COMPLEXING IMAGES IN A TWO-CHANNEL OPTICAL-ELECTRONIC SYSTEM AS A METHOD OF REDUCING THE PROBABILITY OF DISAPPOINTING AN AUTOMATIC SURVEILLANCE OF LOW CONTRAST OBJECTS - A. V. Khizhniak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The paper discusses the work of the correlation algorithm for automatically tracking objects of interest in a two-channel optical-electronic system in a complex background-target environment and the presence of intentional interference. Conditions in which the contrast of the desired object in both channels is negligible but not equal to zero are considered difficult in the paper. Intentional interference refers to masking interference of natural and artificial origin, which helps to reduce the contrast of the object in both channels. By two-channel means an optical-electronic system, which includes channels of the visible and infrared ranges. It is believed that the multi-spectral images of both channels are reduced to a single time and scale, which allows them to be integrated using various methods. The purpose of this paper is to prove that the likelihood of disruption of automatic tracking is reduced when complexing the source images of the visible and infrared ranges, when the contrast of the desired object in both channels is negligible. For research the mathematical apparatus of the theory of random functions and simulation with subsequent statistical data processing are used. It is shown that the probability of disruption, characterized by the ratio of the correlation coefficients of two fragments of images, one of which contains the desired object, and the second not, depends on both the correlation coefficients and the values of their mean square deviations. The simulation shows that the breakdown of tracking occurs both when the mean square deviations of these correlation coefficients are equal, and at their different values, moreover, an increase in their difference increases the probability of a breakdown. The article shows that the likelihood of a breakdown in a two-channel optoelectronic system will decrease when using two channels, compared to working only in the visible or infrared channel. The obtained results substantiate the promise of using image complexing in multichannel systems of automatic tracking of objects in a complex background-target environment and the presence of deliberate interference.